Augmentation of the urban green infrastructure using stormwater surface runoff as a resource in the NICE expressway, Karnataka, India - Shreewatsav, Malavica; Sheriff, Vaseem Anjum (Journal of Environmental Engineering and Landscape Management, 2022)
Urban areas, characterized by impervious surfaces, produce storm water runoff which during unexpected heavy rainfall exceeds the carrying capacity of the storm water drainage system causing urban flooding. Transport expressways are massive hard-scaped surfaces generating large amounts of polluted surface run-off during the rains. In the case of the Nandi Infrastructure Corridor Enterprises (NICE) Expressway at Bengaluru, India, which is also a tolled road, the demonstration is about using the surface run-off or stormwater as a resource for developing urban green infrastructure complementing the transport grey infrastructure. The functions of urban green infrastructure include air quality improvement, microclimate modification, storm water management, biodiversity, recreational opportunities and visual aesthetics. Here we show, that the surface runoff or stormwater is effectively channelled to the areas around, to mark the beginning of a well-planned and executed drainage system, maintenance-free landscape and technically a sound, urban green infrastructure in the form of site-specific models of Rain Gardens. The same models can be used in other transport expressways as they are the indicators of economic growth and connectivity although would require to be customized as per the city and its climatic conditions. This paper explores three different scenarios with a typical model of development of green infrastructure along the transport expressway tailormade for each of the situations. While in the first and the second models, the Central Rain Garden and the Edge Rain Garden have been respectively proposed, the third model explores a comparatively complex scenario in the form of an Intersection Rain Garden.